Rancang Bangun Aplikasi Game Virtual Reality Berbasis Android Bertema Petualangan - Dian Gustina; Karno Diantoro; Felicia Meyke Ulfah Maharani (Fakultas Ilmu Komputer, 2019)
Technology is one part that can not be separated from human life. Various fields in human life have been greatly welcomed by technology, computer technology first. Virtual Reality (VR) is a new way to explore the virtual world. With virtual reality, the user seemed to be entering a new environment in the virtual world. The vastness of the virtual world can provide many advantages to produce a variety of fun entertainment.